Photoautotrophic Cultivation of Arthrospira maxima for Protein Accumulation under Minimum Nutrient Availability - Pan-utai, Wanida; Poopat, Natapas; Parakulsuksatid, Pramuk (Applied Food Biotechnology, 2020)
Background and Objective: Arthrospira cyanobacteria are important freshwater blue-green microalgae as food protein sources for humans. Arthrospira maxima phototrophic cultivation was carried out under various minimum media formulations to enhance biomass and protein productions. Macronutrients and micronutrients are vital for biomass production and protein accumulation of Arthrospira maxima for food supplemented uses. Materials and Methods: Photoautotrophic cultivation of Arthrospira maxima IFRPD 1183 was carried out using various Zarrouk culture media and inoculum preparation conditions for biomass and protein productions. Arthrospira maxima IFRPD 1183 was cultivated using algal chamber under closed and open photobioreactor systems. Results and Conclusion: Micronutrients of B6 solution; NH4VO3, K3Cr2 (SO4)4. 24H2O, NiSO4. 7H2O, Na2WO3, Co (NO3)2. 6H2O and Ti2 (SO4)3 did not affect cell growth and protein accumul-ation in absence of media for inoculum production. Inoculum preparation under various conditions of Arthrospira maxima IFRPD 1183 was studied using filtration of the old media before use (cell filtration inoculum) with no filtrations of the old media before use (cell non-filtration inoculum). Cell non-filtration inoculum preparation was reported appropriate for biomass production and protein accumulation. For large-scale productions, open pond system of Arthrospira maxima IFRPD 1183 resulted in maximum biomass and protein production at nearly 1 g l-1 and 64% (DW), respectively, for repeat batch photoautotrophic cultivation. Absence of micronutrients with cell non-filtration inoculum was reported as an easy process to achieve large biomass and protein productions for closed and open photoautotrophic cultivations of Arthrospira maxima at decreased costs.